Fieldtrip in the Mekong Delta (July-August 2022) - Le Phuong Dung (2022)
As part of the PhD climate security research in the Mekong Delta, a fieldtrip was conducted in July – August 2022. The presentation outlines some preliminary observations and results from 38 key informant interviews conducted during the fieldtrip in different provinces in the region.